Factors of perceived organizational politics: An analysis of what contributes the most? - Sarwat Sultan; Frasat Kanwal; Shahzad Gul (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This study explores the contributions of four factors altogether from (1) individual, (2) dispositional, (3) organizational, and (4) job characteristics in organizational politics. A sample of college teachers (n=423) taken from Multan provided data on the measures of individual attributes, perceived organizational politics, Type-A behavior pattern, basic psychological needs at work, organizational structure, and job characteristics. The series of ordinary least squares regression model was employed to analyze the role played from four groups of factors. Results indicated that Findings revealed that age and job tenure from personal factors, Type-A behavior and need of autonomy from dispositional factors, centralization, formalization, and hierarchical level from organization factors, and skill variety, job autonomy, and feedback from job-related factors were found highly significant predictors of perceived organizational politics. Findings support the consideration of personal, dispositional, organizational, and job-related factors to perception of politics. These findings have the implications for institutes and organizations to derogate the political environment at workplace through providing skill variety, autonomy, feedback, and formalization.
Keywords: 330; perception politics; need of autonomy; type-a behavior; centralization; skill variety